A interseccionalidade entre o PROVITA e a Lei Maria da Penha: análise da possibilidade de uma política pública de prevenção e proteção à extrema violência doméstica e familiar - Zini, Amanda Caroline (2021)
This dissertation is based on the discussion of the social construction of domestic and family violence and the possibilities of protection, taking as its starting point the analysis of concepts relating to public policies, witch hunts, the development of globalization and the role of power relations in social construction, seeking to critically analyze the possibility of an intersection between PROVITA - Program for the Protection of Threatened Victims and Witnesses - and the Maria da Penha Law, in order to take advantage of existing policies for an emerging and current problem. Having as a theoretical framework decolonial feminism, the exploration of submissive bodies, the intersectionality of public policies and power relations. The method used to develop the research is analytical, so that a construction beyond the totalitarian system is sought, allowing a free understanding of the theme explored6. As for the procedures to develop the research, bibliographic and documentary methods were used. In view of these aspects, it is concluded that in the face of a historical construction marked by unjustified violence, restrictions, manifestations of heteropatriarchal power, articulations of globalization to maintain patriarchal power relations and a social demonization of women, the development of policies also stood out. public, as well as its importance for political agendas due to its return to political processes, which allowed us to conclude that, in the contemporary social context, there is a possibility of intersection between PROVITA and the Maria da Penha Law, to take advantage of existing policies to protect and prevent domestic and family violence.